First record of subfamily Brachypterainae (Plecoptera: Taeniopterygidae) in Baltic amber: a new genus and species - Chen, Zhi-Teng (Zootaxa, 2018)
Based on a well-preserved female specimen, a new stonefly genus and species of the family Taeniopterygidae, Balticopteryx dui gen. et sp. nov. is described and illustrated, which is also the first report of subfamily Brachypterainae from the Eocene Baltic amber. Diagnostic characters of this new genus are discussed and compared with related taxa.